Correlates and disparities of intention to vaccinate against COVID-19 - Callaghan, Timothy; Moghtaderi, Ali; Lueck, Jennifer A.; Hotez, Peter; Strych, Ulrich; Dor, Avi; Fowler, Erika Franklin; Motta, Matthew (Social science & medicine (1982), 2021)
•More than 30% of the US public does not intend to vaccinate against COVID-19.•Intention to refuse vaccination is highest for women and Blacks.•COVID-19 vaccine refusal is most often due to safety and effectiveness concerns.